2022
DOI: 10.1021/acssynbio.2c00017
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Expression of Transcription FactorID2Improves Natural Killer Cell Differentiation from Human Pluripotent Stem Cells

Abstract: Natural killer (NK) cells are one type of innate lymphoid cells, and NK cell-based immunotherapy serves as a potentially curative therapy for cancers. However, the lack of reliable resources for a large amount of NK cells required for clinical infusion has limited the broader application of NK cells in targeted immunotherapy. Substantial effort has thus been made to generate NK-like cells from human pluripotent stem cells (hPSCs), but detailed molecular mechanisms regulating NK cell differentiation remain elus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…To determine the function of CLTX-T-CAR neutrophils in vivo , we implemented an in situ xenograft model via intracranial injection of luciferase-expressing GBM cells. Neutrophils were administrated intratumorally or intravenously to determine their in vivo antitumor activities compared with hPSC-derived NK cells ( Jung et al, 2022 ) ( Figures S5A – S5E ). Notably, CLTX-T-CAR neutrophils are more effective in killing GBM cells than CLTX-NK-CAR NK cells in vitro , and the combinatory effect between CAR neutrophils and CAR NK cells was not observed.…”
Section: Resultsmentioning
confidence: 99%
“…To determine the function of CLTX-T-CAR neutrophils in vivo , we implemented an in situ xenograft model via intracranial injection of luciferase-expressing GBM cells. Neutrophils were administrated intratumorally or intravenously to determine their in vivo antitumor activities compared with hPSC-derived NK cells ( Jung et al, 2022 ) ( Figures S5A – S5E ). Notably, CLTX-T-CAR neutrophils are more effective in killing GBM cells than CLTX-NK-CAR NK cells in vitro , and the combinatory effect between CAR neutrophils and CAR NK cells was not observed.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, hPSCs have emerged as an alternative cell source for NK cells to address these issues. Due to their innate killing ability, many studies have shown the superior antitumor activities of hPSC-derived NK cells without additional engineering approaches that confer antigen-specific activity [Woll et al, 2005[Woll et al, , 2009Larbi et al, 2012;Hermanson et al, 2016;Zeng et al, 2017;Mat-subara et al, 2019;Zhu et al, 2020a, b;Cichocki et al, 2020;Goldenson et al, 2020;Euchner et al, 2021;Woan et al, 2021;Du et al, 2022;Jung et al, 2022]. A few strategies were developed to enhance in vivo persistence and antitumor activities of hPSC-derived NK cells.…”
Section: Nk Cellsmentioning
confidence: 99%